ITERATIVE SOLUTION OF FUNCTIONAL VOLTERRA-FREDHOLM INTEGRAL EQUATION WITH DEVIATING ARGUMENT - Atalan, Yunus; Karakaya, Vatan (YOKOHAMA PUBL, 2017)
In this paper, we show that the iteration method defined in V. Karakaya, Y. Atalan, K. Dogan and NH. Bouzara, Some Fixed Point Results for a New Three Steps Iteration Process in Banach Spaces, Fixed Point Theory converges to solution of the functional Volterra-Fredholm integral equation with deviating argument in a Banach space. Furthermore, a data dependence result for the solution of this integral equation has been proven.
Keywords: Volterra-Fredholm functional integral equations; iteration method; data dependence; FIXED-POINTS; Mathematics